Highly Efficient Power Conversion from Salinity Gradients with Ion-Selective Polymeric Nanopores - 凌云 闫东晓 王鹏飞 汪茂 文琪 刘峰 王宇钢 (Chinese physics letters, 2016)
A polymeric nanopore membrane with selective ionic transport has been proposed as a potential device to convert the chemical potential energy in salinity gradients to electrical power. However, its energy conversion efficiency and power density are often limited due to the challenge in reliably controlling the size of the nanopores with the conventional chemical etching method. Here we report that without chemical etching, polyimide （PI） membranes irradiated with GeV heavy ions have negatively charged nanopores, showing nearly perfect selectivity for cations over anions, and they can generate electrical power from salinity gradients. We further demonstrate that the power generation efficiency of the PI membrane approaches the theoretical limit, and the maximum power density reaches 130m W/m2 with a modified etching method, outperforming the previous energy conversion device that was made of polymeric nanopore membranes.